Quantifying atmospheric methane emissions from oil and natural gas production in the Bakken shale region of North Dakota. Issue 10 (25th May 2016) - Peischl, J.; Karion, A.; Sweeney, C.; Kort, E. A.; Smith, M. L.; Brandt, A. R.; Yeskoo, T.; Aikin, K. C.; Conley, S. A.; Gvakharia, A.; Trainer, M.; Wolter, S.; et al.
Abstract: We present in situ airborne measurements of methane (CH4 ) and ethane (C2 H6 ) taken aboard a NOAA DHC‐6 Twin Otter research aircraft in May 2014 over the Williston Basin in northwestern North Dakota, a region of rapidly growing oil and natural gas production. The Williston Basin is best known for the Bakken shale formation, from which a significant increase in oil and gas extraction has occurred since 2009. We derive a CH4 emission rate from this region using airborne data by calculating the CH4 enhancement flux through the planetary boundary layer downwind of the region. We calculate CH4 emissions of (36 ± 13), (27 ± 13), (27 ± 12), (27 ± 12), and (25 ± 10) × 10 3 kg/h from five transects on 3 days in May 2014 downwind of the Bakken shale region of North Dakota. The average emission, (28 ± 5) × 10 3 kg/h, extrapolates to 0.25 ± 0.05 Tg/yr, which is significantly lower than a previous estimate of CH4 emissions from northwestern North Dakota and southeastern Saskatchewan using satellite remote sensing data. We attribute the majority of CH4 emissions in the region to oil and gas operations in the Bakken based on the similarity between atmospheric C2 H6 to CH4 enhancement ratios and the composition of raw natural gas withdrawn from the region. Key Points: CH4 emissions from the Bakken region of North Dakota quantified First emission estimate using in situ CH4 measurements CH4 sources dominated by oil‐ and gas‐related activities